Mozart's Music of Friends: Social Interplay in the Chamber Works - Klorman, Edward (Cambridge Cambridge University Press, 2016)
In 1829 Goethe famously described the string quartet as 'a conversation among four intelligent people'. Inspired by this metaphor, Edward Klorman's study draws on a wide variety of documentary and iconographic sources to explore Mozart's chamber works as 'the music of friends'. Illuminating the meanings and historical foundations of comparisons between chamber music and social interplay, Klorman infuses the analysis of sonata form and phrase rhythm with a performer's sensibility. He develops a new analytical method called multiple agency that interprets the various players within an ensemble as participants in stylized social intercourse - characters capable of surprising, seducing, outwitting, and even deceiving one another musically. This book is accompanied by online resources that include original recordings performed by the author and other musicians, as well as video analyses that invite the reader to experience the interplay in time, as if from within the ensemble.
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; 18th Century (1701-1800); Chamber music; Cultural history; Vienna (Austria)